"The Mother of Us All": (Og)Reta McNeill, Canada's First Professional Music Librarian - McMorrow, Kathleen (CAML Review / Revue de l'ACBM, 2022)
This paper presents extensive new biographical information, assembled from newspaper articles, about Ogreta McNeill, Canada’s first professional music librarian: pianist, singer, teacher, single mother, Toronto Public Library branch director, writer and bibliographer, impresario, founder and first chair of the Canadian Music Library Association. The early accomplishments and influences of her formative years in Victoria BC offer were fully realized in her later identity as a generous contributor to the wider musical community.